2023
DOI: 10.3390/w15142528
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Migration and Transformation in Low Permeability Sediments: Laboratory Experiments and Modeling

Abstract: The excessive application of fertilizers and the uncontrolled discharge of untreated wastewater on land contribute to the nitrogen pollution of groundwater. Low permeability sediment plays an important role in slowing down the migration of nitrate in groundwater systems. This study focuses on the mechanisms that affect nitrate transport in the low permeability layer. A soil column experiment was conducted and an MT3D transport model (a modular three-dimensional multispecies transport model) of nitrate was prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Considering chemical reactions (Scenario 2), a total of 639 g of nitrate was lost from the SGW to the stream from 2020 to 2021; however, 1406 g of nitrate was lost due to denitrification (Figure 9b). These findings align with previous research [52][53][54], where denitrification was identified as the primary nitrogen sink. In January and February 2020, NO 3 -N loss from SGW to the stream initially exceeded denitrification (Figure 9b).…”
Section: Nutrient Transportsupporting
confidence: 92%
See 3 more Smart Citations
“…Considering chemical reactions (Scenario 2), a total of 639 g of nitrate was lost from the SGW to the stream from 2020 to 2021; however, 1406 g of nitrate was lost due to denitrification (Figure 9b). These findings align with previous research [52][53][54], where denitrification was identified as the primary nitrogen sink. In January and February 2020, NO 3 -N loss from SGW to the stream initially exceeded denitrification (Figure 9b).…”
Section: Nutrient Transportsupporting
confidence: 92%
“…The reaction rate constant was specified as 0.07 day −1 . This value is approximately the average rate of denitrification found in soils and aquifers worldwide and represents a half-life of 10 days [12,[54][55][56]. Generally, water flow from the aquifer to the stream (gaining stream) was observed in the study area, specifically for the piezometers close to the stream [31].…”
Section: Nutrient Transport Scenariomentioning
confidence: 78%
See 2 more Smart Citations
“…The key genes present in nitrogen cycling included denitrification genes (such as narH, napA, nirK, nosZ, and norB), nitrogen fixation genes (such as nifD and nifH), ammonia oxidation genes (such as amoA and amoB), and DNRA genes (such as nirB and nirD) [32,33]. Nitrogen fixation and DNRA genes facilitate the formation of NH 3 -N, whereas denitrification and ammonia oxidation genes promote nitrogen removal [34,35]. The relative abundance of nitrogen fixation genes and DNRA genes in the deep sediment layer (−20~−12 cm) was significantly higher than that in the shallow sediment layer (−12~0 cm).…”
Section: Mechanisms Of Improvement In Sediment Microbial Ecological E...mentioning
confidence: 99%